Codigestão anaeróbia de lodo de flotador do abate de frangos e caldo de cana-de-açúcar - Restrepo , Juan Camilo Pires Salcedo (2019)
The Southern region of Brazil, more specifically in the West of Paraná, the largest poles of chicken meat production in the country are located. Among poultry slaughterhouse waste, floating sludge (FS) stands out due to the quantity and technical complexity of its treatment and stabilization. Anaerobic digestion is considered a sustainable alternative technology for the treatment of organic residues, with the ability to recover the substrates processed energetically and agronomically. The high levels of lipids and proteins attribute to the FS a low C/N ratio, which can lead to inhibitions by several factors during the anaerobic digestion process, interfering with the biogas production and the efficiency of the digestate stabilization. In order to compensate for the deficiency in carbon, the insertion of sugarcane juice (SCJ) (Saccharum officinarum, L.) in the digestion process is suggested. The SCJ is rich in sucrose, a labile carbonaceous source that during fermentative processes undergoes rapid hydrolysis due to its high bioavailability. The present work aimed to study the process of anaerobic codigestion of the FS together with the increasing volumetric quantities of SCJ (among treatments) in order to complement the digestates with a source of carbon which was labile and soluble. The influence of inhibitory parameters that could destabilize or collapse the anaerobic digestion process was also evaluated, directly influencing the energy recovery and agronomic recovery of the substrate. The semi-continuous assay consisted of tubular reactors of 60 L working volume, arranged parallel and horizontally, conducted at constant mesophilic temperature, hydraulic retention time of 25 days and daily feed (2.4 L total) containing 4.5% of total solids (TS) of FS (for all treatments monodigestion, 1, 2, 4, and 6% SCJ), being part of the load (60%) constituted by the recycle from the previous day. It was observed that, despite the high concentrations of ammoniacal nitrogen (≈ 950 – 1300 mg L-1) and free ammonia (≈ 165 – 215 mg L-1), there was no direct inhibition relationship in biogas and methane yield. Although the high values of volatile acidity (≈ 6 – 6.95 g L-1) had consumed the alkalinity of the 4 and 6% SCJ treatments and significantly influenced their pH, there was no inhibitory phenomenon related to the acidification of the digestate. The treatment that received 2% SCJ showed the highest production values (0.094 m³ day-1), productivity (0.94 m³ N CH4 / m³ reactor day) and yield (0.58 m³ N CH4 / kg VSadc.) when compared to the others, as well as its nutrient recovery also corresponded to the larger cultivable areas of Saccharum officinarum, L. with the biofertilizer produced (11.46 ha – 80 Kg N ha -1). Finally, it is concluded, that the codigestion under study becomes a possible alternative of treatment to the energetic and agronomic recovery of the FS.